A.L.T a memoir - Talley, André Leon 1949-2022 (Villard, 2003)
The editor-at-large for "Vogue" describes his odyssey from North Carolina to the heights of the fashion world, reflecting on how his life was influenced by his maternal grandmother, Bennie Frances Davis, and Diana Vreeland, his mentor.
Keywords: Davis, Bennie Francis <d. 1989>; Talley, André Leon; Vreeland, Diana; African American fashion editors -- Biography; Fashion editors -- United States -- Biography; USA; Biografie